Evaluasi Usability Menggunakan Metode Think Aloud dan Heuristic Evaluation pada Aplikasi Mobile Padiciti - M. Iqbal Farras Pratama; Hanifah Muslimah Az-Zahra; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Padiciti mobile application is one of the m-ticketing applications released in 2013 which currently has more than 100,000 users on the Google Playstore. From the initial observations made on Google Playstore there were user dissatisfactions such as low ratings and dissatisfaction comments regarding problems when using the Padiciti mobile application. This problem is related to usability. Evaluation is needed, one of which is to use the method of thinking aloud (user) and supported and strengthened by the perspective of usability experts using the heuristic evaluation method. The results of think aloud found 145 problems that can be grouped again into 35 problems because there are similar problems. As many as 3 of the 12 task scenarios failed by the user because the feature cannot run and there are 2 users who failed to run the task scenario 6 because there was a force close. While evaluation using heuristic evaluation found 64 problems that can be grouped again into 30 problems because there are similar problems. From the grouping of problems obtained from think aloud and heuristic evaluation there were 40 problems. Consisting of 25 similar problems found by users and experts, 10 problems that were found by users only and 5 problems found by experts only. Problems with severity rating of 4 ​​are 3 problems, severity rating of 3 ​​are 11 problems, severity rating of 2 ​​are 17 problems and severity rating of 1 are 9 problems. These problems are categorized into 3 categories, namely the functional side, the display side and the information side. On the functional side there are 16 problems, on the display side there are 11 problems and on the information side there are 13 problems.